Períodos de actividad y dieta de Dasyprocta punctata (Gray, 1842) (Rodentia; Dasyproctidae) en agroecosistemas con café, San Ramón, Costa Rica - Sánchez-Brenes, Ronald J.; Monge, Javier (Instituto de Ecología, A.C., 2021)
The guatusa Dasyprocta punctata (Gray, 1842) is a species classified as having a stable population and present in different habitats, however, its habits (diet, periods of activity and behavior) have been little described. This research is based on determining D. punctata habits in coffee agroecosystems in Rincón de Mora, San Ramón, Alajuela, Costa Rica. For this, four camera traps were placed in strategic places (food sources, burrows, creeks, and transition with the secondary forest). The review of the videos revealed new dietary habits that had not been recorded for this species, including the consumption of Polyporus sp. Likewise, it was observed that the greatest period of annual activity in the coffee plantation occurs in the phenological stage with fruit, while the period of daily activity broadened the spectrum in hours of the night. Similarly, already identified behaviors were recorded, where one of the most important is seed dispersal.